Cu2+-dependent stereoselective hydrolysis of a chiral organophosphonothioate insecticide for domestic mammals' sera and its albumins. (September 2021) - Undiano, Elizabeth; Chávez, Susana; Mederos, Pedro; Ayala, Marcela; Monroy-Noyola, Antonio
Abstract: Acute toxicity of organophosphate (OPs) pesticides is a public health problem. The adverse effects are associated with the inhibition and aging of nervous system B-esterases such as acetyl cholinesterase (AChE) and neuropathic target esterase (NTE). Treatment based on A-esterases such as mammal serum paraoxonase-1 has been suggested. This ex vivo study shows the Cu 2+ -dependent hydrolysis of trichloronate (TCN), a racemic organophosphonothioate insecticide, in human and domestic mammal serum (dog, goat, pig, sheep and cow). Ca 2+ -dependent (2.5 mM) or EDTA-resistant (5 mM) activity (1–6%) was not significant (p>0.05) in all samples, except goat serum and its albumin, which showed higher levels of TCN hydrolysis (38–58%) than other mammals with 100 and 300 μM copper sulfate at physiological conditions for 60 min. Goat serum albumin (GSA) showed significant (p˂0.05) stereoselective hydrolysis (+)-TCN ˃ (−)-TCN (45% versus 33%). This suggests that GSA is the protein responsible for Cu 2+ -dependent TCNase activity in goat serum. This is the first report on Cu 2+ -dependent A-esterase activity in mammalian tissues. This goat serum cuproprotein could be considered as an alternative in future biotechnological applications including enantiomeric synthesis, bioremediation and antidotal treatment of organophosphonothioate pesticide poisoning. Highlights: Hydrolysis of a chiral organophosphonothioate for mammal's sera. Cu 2+ -dependent stereoselective hydrolysis of trichloronate by mammal serum albumins. Goat serum albumin with Cu2+-dependent A-esterase activity.